2021
DOI: 10.3906/fiz-2110-16
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Weak Deflection Angle by Black Holes or Wormholes using Gauss-Bonnet Theorem

Abstract: In this review, various researches on finding the bending angle of light deflected by a massive gravitating object which regard the Gauss-Bonnet theorem as the premise have been revised. Primarily, the Gibbons and Werner method is studied apropos of the gravitational lensing phenomenon in the weak field limits. Some exclusive instances are deliberated while calculating the deflection angle, beginning with the finite-distance corrections on nonasymptotically flat spacetimes. Effects of plasma medium is then ins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…[59]. In another work, the weak deflection angle by black holes and wormholes has been extensively studied with different examples and wormhole structures [60]. Apart from these, there are several studies dealing with deflection angle in the domain of black holes and wormholes [61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
“…[59]. In another work, the weak deflection angle by black holes and wormholes has been extensively studied with different examples and wormhole structures [60]. Apart from these, there are several studies dealing with deflection angle in the domain of black holes and wormholes [61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for asymptotically flat black hole spacetimes, many studies have shown that the integration of geodesic curvature κ g along the circular arc C R in the R → ∞ limit reduces to [83,90] ∂D…”
Section: Jcap12(2023)005mentioning
confidence: 99%